Influence of lupin and rapeseed meals on the integrity of digestive tract and organs in gilthead seabream (Sparus aurata L.) and goldfish (Carassius auratus L.) juveniles. (22nd May 2014) - Omnes, M.H.; Silva, F.C.P.; Moriceau, J.; Aguirre, P.; Kaushik, S.; Gatesoupe, F. J.
Abstract: Two rearing trials were conducted to evaluate the effects of dietary lupin (LM) and rapeseed (RM) meals in gilthead seabream ( Sparus aurata L.) and goldfish ( Carassius auratus L.) juveniles. Each plant meal was incorporated at the rate of 200 g kg −1 in two distinct diets, which were compared with a fishmeal‐based diet as control. After 1 month, the two plant diets did not influence the whole body growth, but the digestive systems were affected. The splenosomatic index was reduced with two plant meals in goldfish and with RM in seabream. The hepatosomatic index was only reduced in LM‐fed seabream. Cellular characteristics were also affected. The largest liver cells were observed in RM‐fed goldfish suggesting changes in metabolic function. The LM and RM diets stimulated in seabream, especially the reaction in haematopoietic tissues with the proliferation of melano‐macrophages centres, and a tendency for elongated villus height in the anterior intestine thus that possibly compensated for a reduction in digestive function. Such adaptive structural modifications and the absence of degenerative signs allowed concluding that the integrity of the digestive system was maintained in fish fed plant meals.